2013
DOI: 10.1186/1471-2172-14-31
|View full text |Cite
|
Sign up to set email alerts
|

Limiting prolonged inflammation during proliferation and remodeling phases of wound healing in streptozotocin-induced diabetic rats supplemented with camel undenatured whey protein

Abstract: BackgroundImpaired diabetic wound healing occurs as a consequence of excessive reactive oxygen species (ROS) and inflammatory cytokine production. We previously found that whey protein (WP) was able to normally regulate the ROS and inflammatory cytokines during the inflammatory phase (first day) in streptozotocin (STZ)-diabetic wound healing. This study was designed to assess the effect of WP on metabolic status, the inflammation and anti-inflammation response, oxidative stress and the antioxidant defense syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 41 publications
5
39
0
1
Order By: Relevance
“…C (500 mg/kg) exerted significant improvement in liver and brain SOD activity in TAAtreated rats, while their combination maintained normal SOD activity in liver tissues. Current data is in accordance with other investigators who reported that whey proteins, including α-LAC, suppressed hepatic lipid peroxidation and stimulated the antioxidant defense system by increasing the level of glutathione and the activity of glutathione-S-transferase (GST), glutathione peroxidase (GPx) and superoxide dismutase (SOD) in wounded diabetic rats (Ebaid et al, 2013),α-LACattenuated the decrease in hepatic SOD activity in TAA-induced fibrosis and improved hepatic SOD activity in LPS-treated rats . In addition, vit.…”
Section: Resultssupporting
confidence: 92%
“…C (500 mg/kg) exerted significant improvement in liver and brain SOD activity in TAAtreated rats, while their combination maintained normal SOD activity in liver tissues. Current data is in accordance with other investigators who reported that whey proteins, including α-LAC, suppressed hepatic lipid peroxidation and stimulated the antioxidant defense system by increasing the level of glutathione and the activity of glutathione-S-transferase (GST), glutathione peroxidase (GPx) and superoxide dismutase (SOD) in wounded diabetic rats (Ebaid et al, 2013),α-LACattenuated the decrease in hepatic SOD activity in TAA-induced fibrosis and improved hepatic SOD activity in LPS-treated rats . In addition, vit.…”
Section: Resultssupporting
confidence: 92%
“…Diverse physiological factors that contribute to wound-healing delay include but are not limited to impaired growth factor production, collagen accumulation, keratinocyte migration and proliferation and angiogenic response. A major determining factor for such a delay is a prolonged inflammatory phase that increases the time required for wound closure during diabetes (35). This step impedes the start of the next phase of wound healing, thereby causing a delay in granulation and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The impaired immune system in diabetic mice was associated with an increase in blood glucose levels, a decrease in insulin levels, and a decrease in body weight, which were partially reversed by CWP treatment. Likewise, CWP stimulated insulin release and lower blood glucose levels in type 1 diabetic rats [39, 40]. It also decreased elevated levels of IL-1β, IL-6, and TNF-α in diabetic mice.…”
Section: Discussionmentioning
confidence: 99%